PATTERNS OF PREY BIOMASS CONSUMPTION BY SMALL ODONTOCETES IN THE NORTHEASTERN COAST OF VENEZUELA - Oviedo-Correa, Lenin Enrique (2009)
Trophic relationships are conditioned by population dynamics of interacting species in the community (species present, food web connections among them, and the strength of interactions), and on the consequences of these species interactions depend various ecosystem processes such as productivity and nutrient flux. Odontocetes target a wide range of prey items and are adapted to feeding at different depths. The aim of this report is to describe the patterns of prey consumption by small odontocetes, incorporating natural predatory patterns into a potential management scheme of strategic food sources, for both human and marine predators. Using the geo-statistical analysis tool of ArcGIS 9.2, maps illustrating the intensity and location of prey consumption were made for species with a sighting index (SPUE) > 0.15. The biomass consumption emphasized the differences in habitat use by species. The trends in distribution of prey biomass removal by odontocetes particularly suggest a stratification of prey consumption primarily in shelf waters, with a prey biomass that is comprised basically by demersal fish and small pelagics (including Sardinella aurita), and into transition-oceanic depths where most of the predatory pattern would potentially rely on pelagic - mesopelagic squid and myctophids. Overall the spatial tendencies in regionalization presented in this contribution will serve as a base-line to assess ecosystem health and evaluate management scenarios.